PERANCANGAN TATA LETAK GUDANG BAHAN BAKU DENGAN METODE SHARED STORAGE PADA PT. PANTJATUNGGAL KNITTING MILL - Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2018)
Warehouse layout is one very important issue to be considered, because the layout affect the operating efficiency in the long run. The problems faced by PT Pantjatunggal Knitting Millin raw material storage. Raw materials that have a frequency shift that is often placed far from the I/O, the distance is too much movement of goods and the amount of material handling costs.Shared storage method is a method used to regulate the storage warehouse to be more effective. Switching frequency of fast-moving material is stored in a warehouse which is closer to the frequency shift and slow-moving material is stored in a warehouse furtherfrom the process. The result of the analysis and design of warehouse layout of raw materials is a new layout with shared storage methods, the distance the movement of good initially for 1.150 meters to 691,6 meters or having a saving of 39,8% from the previous layout. As for the original cost of Rp. 37.375,00 to Rp 21.519,00 or experiencing a saving of 42,5%. Thus the layout of the shared storage method is expected to be used as consideration for the company to reorganizethe layout of the raw materials warehouse PT Pantjatunggal Knitting Mill. Keywords:Layout, Material Handling, Shared Storage Method